A virus disease of phaseolus vulgaris L. in the Transvaal - Cowper, Beverley Anne (My University, 2015)
Viral pathogens axe known to infect Phaseolus spp* worldwide. A local survey was conducted to determine if viruses were associated with any disease symptoms in local varieties Phaseolus spp. From the regions sampled, only flexuous rods and a spherical particle were isolated.